The Impact Of Application Of Fair Value Accounting On Qualitative Characteristics Of Accounting Information And Obstacles Of Its Applying In Syrian Business Environment According To The Syrian Certified Accountants’ Point Of View - الحكيم سلمان (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aims to know the effect of application of fair value accounting on qualitative characteristics of accounting information, in addition to determining the most important obstacles of its application in Syrian business environment according to Syrian certified accountants’ point of view. For realizing the aim of study, the researcher depended on questionnaire as a tool for collecting data. The questionnaire has included (33) variables, (20) variables to measure the effect of application of fair value accounting on qualitative characteristics of accounting information, (13) variables to measure suitability of Syrian business environment for applying fair value accounting. The questionnaire has been distributed to (70) certified accountants by coordinating with the Association of Syrian Certified Accountants (ASCA), and the survey forms which were refundable and valid for analysis have amounted (46) forms. According to the results of analyzing data and testing hypothesis which have been done by using SPSS program, there is a positive effect for applying fair value accounting on quality of accounting information, but there are legal, economic, cultural, and professional obstacles inhibit application of fair value accounting in Syrian business environment.